Radiological and clinical outcomes following pelvic support osteotomy with limb length equalization in children - Vikaas Ethanur Thuppale; Arulmurugan Arikrishnan; Jonathan Reddy; Abhay Gahukamble; Thomas Palocaren (Journal of Pediatric Orthopaedics B, 2026)
Pelvic support osteotomy (PSO), when done in children, is subject to remodeling. This study aimed to assess the extent of remodeling at the osteotomy site and functional outcome post-PSO. A total of 28 patients were selected with a minimum follow-up of 2 years. PSO was combined with limb length equalization procedures including distal femoral lengthening, epiphysiodesis, or shoe raise, as indicated, because all patients had limb length discrepancy as part of their underlying pathology. The valgus osteotomy angle incorporated into the proximal femur was measured on the immediate postoperative standardized pelvis anteroposterior X-ray and at serial follow-ups. All observations were made by two observers. Functional outcome assessment was done with the preoperative and 2-year postoperative Harris Hip scores. Twenty-eight children with a mean age of 11.8 years (range: 6–16 years) were included in the study. The overall mean reduction in osteotomy angle was 2, 6.3, and 11° at 3 months, 1 year, and 2 years follow-ups, respectively. Children less than or equal to 12 years of age had a mean reduction of 12.4° compared with 9.3° in children more than 12 years of age; males had a mean reduction of 12.5° compared with 9° in females, at 2-year follow-up. The mean Harris Hip scores were 57.71 and 88.79, preoperative and 2-year postoperative, respectively. PSO combined with limb length equalization provides good functional improvement in children with severe postseptic sequelae of the hip. However, significant osteotomy remodeling may compromise long-term correction and necessitate repeat procedures, particularly in younger children, highlighting the importance of careful patient selection.